Analysis and Correction of the Additive Phase Effect Generated by Power Change in a Mach–Zehnder Interferometer Integrated to an Optical Trap - Cordero-Carrasco, R (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Immersion microscope objectives stand out for their large numerical aperture, which improves the optical resolution of imaging systems such as those used in microscopic interferometry. These objectives increase the gradient forces of a beam focused through them, forming an Optical Trap (OT). However, many studies on microscopic interferometry neglect the contributions of different optical materials in the system that are also exposed to laser radiation, perhaps simply assuming transparency. In this work, a Mach–Zehnder interferometer and an OT, which share several components (including the same oil immersion objective), were coupled. Here, the response of the interferometer to a progressive increase in the OT laser power, while the interferometer laser power remains constant, is reported. Changes in laser power affect the oil temperature, altering its refractive index and volume, which in turn causes a phase shifting on the transmitted wavefront. Optical phase analysis is applied in the three-dimensional measurement of the damage produced by the OT on a paint film. This study suggests that the refractive index variations in the immersion oil affect interferograms because they will then exhibit an additive phase term that must be considered in that final measurement. Additionally, the OT geometry changes with the power increase. © 2024 by the authors.